مقومات الأبداع الأداري وعلاقتها بالحمارسات التكنولوجية الحديثة لدى مديري المدارس من وجهة نظر الحعلممين بسلطنة عمان - Mizoon Amer Bakhit Al-Maanshani (Universiti Sains Islam Malaysia, 2024)
Despite the importance of technology to administrative innovation, school principals demonstrate incompetence in innovative practices including not setting priorities of development and the lack of using technology related to school performance. Thus, this research aims to reveal the level of components of administrative innovation held by school principals, and to diagnose the reality of practicing administrative innovation by school principals using modern technology. Moreover, the research aims to evaluate the correlative relationship between components of administrative innovation and practices of modern technology and to analyze the differences among teachers’ opinions about components of administrative innovation and practices of modern technologies based on the variables of the study. Furthermore, the study lists the main challenges that school principals face when using instructional technology in schools of basic education. The study adopts the correlative descriptive approach by applying a questionnaire for collecting data. The questionnaire was distributed to a random sample of 474 that was derived from the study population. Also, the questionnaire consists of 57 statements distributed to three dimensions for collecting the required data. The validity and reliability of the instrument were verified by using Cronbach’s Alpha. The results of the study indicate that school principals do possess the components of administrative innovation indicating high level, as the mean was 3.887, and high level in the dimension of practices of administrative innovation using modern technology as the mean was 4.063. The results also proved that there is a direct relation between the components of administrative innovation and the use of technology. Furthermore, the results showed that there are statistically significant differences among teachers’ opinions about components of administrative innovation as a whole that are attributed to the Type variable in favour of principals, and in the field of fluency that are attributed to the Career Experience variable. However, in the dimension of modern technology practices, the differences were in determining the needs of electronic work and activating electronic devices that are attributed to the Type variable in favour of principals. The results also showed that there are some challenges that school principals face including activating modern technology, as the mean was 2.320. Another challenge is the poor Internet connection and network interruptions that go for uncertain periods where the mean was 3.570. This would influence the administrative innovation using modern technology in a moderate level. Key recommendations include, supporting administrative innovation using modern technology, hiring technicians to alleviate any problems that hinder the use of modern technology, and recruiting trainers to conduct training workshops to improve the components of administrative innovation of school principals.